RNAi technology targeting PbGP43 and PbP27 in Paracoccidioides brasiliensis (2013)
ABSTRACT : Efficient technologies for gene silencing would be important to carry out functional analysis with P. brasiliensis genes, as well as for a better understanding of the biology and pathogenesis of this pathogenic fungus. Due to the fact that homologous recombination is unusual in P. brasiliensis, the development of knockout isolates is currently non-feasible. The goal of this work was to assess RNA interference (RNAi) technology as an alternative tool for gene silencing previously employed successfully in H. capsulatum. For this purpose, we built different inverted repeat transgenic hairpin constructs to down-regulate the PbGP43 and PbP27 genes known to codify for two fungal immunogenic proteins that elicit a strong immune response during experimental paracoccidioidomycosis. Using the RNAi strategy, a reduction in the mRNA levels of the PbGP43 and PbP27 genes was observed during the first 20 days after selection; however, in the transformed yeast cells, the gene silencing status proved non-stable through the assay. We demonstrated that electrotransformation was suitable to transform P. brasiliensis yeast cells and integrate the hairpin constructions; nonetheless, gene silencing was not stable along the experimental time. A detailed analysis of the underlying molecular RNAi machinery may provide further insights into the intracellular mechanism that governs this reverse genetic tool.